An exploration of the views of Australian mothers on promoting child oral health. (26th February 2016) - Virgo‐Milton, M; Boak, R; Hoare, A; Gold, L; Waters, E; Gussy, M; Calache, H; O'Callaghan, E; de Silva, AM
Abstract: Background: An important role for parents and caregivers in the prevention of dental caries in children is the early establishment of health promoting behaviours. This study aimed to examine mothers' views on barriers and facilitators to promoting child and family oral health. Methods: Semi‐structured interviews were undertaken with a purposive sample of mothers (n = 32) of young children. Inductive thematic analysis was conducted. Results: Parental knowledge and beliefs, past experiences and child behaviour emerged as major influences on children's oral health. Child temperament and parental time pressures were identified as barriers to good oral health with various strategies reported for dealing with uncooperative children at toothbrushing time. Parental oral health knowledge and beliefs emerged as positive influences on child oral health; however, while most mothers were aware of the common causes of dental caries, very few knew of other risk factors such as bedtime feeding. Parents' own oral health experiences were also seen to positively influence child oral health, regardless of whether these were positive or negative experiences. Conclusions: Understanding parental oral health beliefs is essential to overcoming barriers and promoting enablers for good child oral health. Improving child oral health also requires consideration of child behaviour, family influences, and increasing awareness of lesser‐known influencing factors.